"Scotland Small? Our Multiform, Our Infinite Scotland Small?" Scotland's Literary Contribution to the Modern World - Aniela Korzeniowska (Colloquia Humanistica, 2015)
"Scotland Small? Our Multiform, Our Infinite Scotland Small?" Scotland's Literary Contribution to the Modern World